Usulan Prioritas Supplier Berdasarkan Interpretive Structural Modeling Dan Analytical Network Process Di Pt Xyz - RAHADYAN RAMADHAN, ZIDAN; HERNI MUSTOFA, FIFI (e-Proceeding FTI, 2024)
PT XYZ is a company engaged in the garment industry. To meet the needs of raw materials, the company uses four supplier companies. Each supplier has its own advantages and disadvantages. Currently, the company has not consistently used criteria and has not determined the best supplier priorities in determining its suppliers. The purpose of the research conducted was to propose the priority of raw material suppliers based on Interpretive Structural Modeling (ISM) and Analytical Network Process (ANP) at PT XYZ. Interpretive Structural Modeling (ISM) calculations produce six key subcriteria such as Product quality according to specifications, number of defective products obtained, timeliness of delivery, low prices, raw materials always available, and capacity fulfillment capabilities. The calculation of the Analytical Network Process (ANP) produces a sequence of the best alternative suppliers based on weight. Keyword: Supplier, Interpretive Structural Modeling (ISM), Analytical Network Process (ANP), supplier selection, subcriteria PT XYZ merupakan perusahaan yang bergerak pada bidang industri garmen. Untuk memenuhi kebutuhan bahan baku, perusahaan menggunakan empat perusahaan supplier. Setiap supplier memiliki kelebihan serta kekurangannya tersendiri. Saat ini, perusahaan belum konsisten menggunakan kriteria dan belum menentukan prioritas supplier yang terbaik dalam penentuan supplier-nya. Tujuan penelitian yang dilakukan adalah mengusulkan prioritas supplier bahan baku berdasarkan Interpretive Structural Modeling (ISM) dan Analytical Network Process (ANP) di PT XYZ. Perhitungan Interpretive Structural Modeling (ISM) menghasilkan enam subkriteria kunci seperti Kualitas produk sesuai spesifikasi, jumlah produk cacat yang didapat ketepatan waktu pengiriman, harga murah, bahan baku selalu tersedia, dan kemampuan pemenuhan kapasitas. Perhitungan Analytical Network Process (ANP) menghasilkan urutan dari alternatif supplier terbaik berdasarkan bobot. Kata kunci: Supplier, Interpretive Structural Modeling (ISM), Analytical Network Process (ANP), pemilihan supplier, subkriteria.